Effectiveness of emotional intelligence education in enhancing positive life skills of Nigeria prison inmates (2007)
The study investigated the effectiveness of Emotional Intelligence education in enhancing positive life skills of some Nigerian prison inmates. Ninety-one (91) prisoners from Agodi prisons, Ibadan, Oyo State and Ilesa, Osun State whose ages ranged between 18-21 years with a mean of 19.5 were randomly assigned to the intervention condition and the control group. The training lasted for six weeks of 12 sessions. A pre-test, post-test control group design using a 2x3 factorial was adopted. The participants responded to sections A (self concept scale) of Akinboye's Adolescent Personal Data Inventory and Akinboye's Emotional Intelligence test, both at the pre and post intervention sessions. The result indicated that the intervention group performed significantly better than the control group on Akinboye's Emotional Intelligence Test {(1,85) = 182.08 P < 0.05}. On the basis of the findings, it was suggested that Nigerian prisoners should be exposed to Emotional Intelligence education which has been found to be effective. Through this training, it is believed that their positive life skills could be stimulated, enhanced and fully developed to make them better and responsible citizens useful to themselves and the society after incarceration